Integrated Metabolomic and Transcriptomic Analysis Reveal the Production Mechanism of Semicarbazide in Macrobrachium rosenbergii Under Urea Conditions - Jun Li; Di Wang; Shengjun Chen; Fangfang Gao; Chunsheng Li; Yang Feng; Jianchao Deng (Foods)
Semicarbazide (SEM) is commonly utilized as a biomarker for detecting the usage of nitrofurazone (NFZ); however, its endogenous presence in aquatic products complicates detection and poses challenges to the quality and safety of these products. Although previous research suggests a potential link between SEM and urea, the specific mechanisms underlying its production under induced conditions remain unclear. To solve the above problem, the integrated metabolomic and transcriptomic analyses were performed for systematically exploring endogenous production mechanisms underlying SEM in Macrobrachium rosenbergii under urea conditions. As a result, urea exposure significantly disrupted key pathways, including glycine, serine, and threonine metabolism; 2-oxocarboxylic acid metabolism; and protein digestion and absorption, thereby highlighting the role of amino acid metabolism in SEM formation. Compared to traditional single-omics approaches, this method provided a comprehensive analysis of gene–metabolite interactions, revealing the mechanism of endogenous production of SEM in M. rosenbergii. This research offers new insights into enhancing aquatic product safety and quality and represents a methodological reference for future research regarding the endogenous SEM production mechanisms.